2013
DOI: 10.1097/bot.0b013e318291f263
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Insufficiency in Patients With Acute Hip Fractures of All Ages and Both Sexes in a Sunny Climate

Abstract: Prognostic level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
1
13
1
1
Order By: Relevance
“…Low 25 (OH) vitamin-D levels have been documented in various studies on hip fracture [2,11,[24][25][26][27]. A high prevalence of vitamin-D deficiency and secondary hyperparathyroidism noted in our patients with recent hip fracture implies that these subjects were vitamin-D deficient even before the occurrence of fracture.…”
Section: Vitamin-d Deficiencymentioning
confidence: 66%
“…Low 25 (OH) vitamin-D levels have been documented in various studies on hip fracture [2,11,[24][25][26][27]. A high prevalence of vitamin-D deficiency and secondary hyperparathyroidism noted in our patients with recent hip fracture implies that these subjects were vitamin-D deficient even before the occurrence of fracture.…”
Section: Vitamin-d Deficiencymentioning
confidence: 66%
“…The Fisher and Belle formula was used to estimate the required sample size using the following variables: 60% risk for vitamin D inadequacy (40-80%) in patients with hip fracture, 95% confidence interval and 10% sample error [10,15]. The result was 92 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Classical actions of vitamin D include intestinal calcium absorption by aiding the active transport of this ion through the enterocytes, bone resorption, and calcium reabsorption at the distal renal tubules in the presence of parathormone [10,11]. However, currently, beyond these known effects, data from ecological and observational studies have demonstrated associations between vitamin D deficiency and cancer, cardiovascular diseases, neurodegenerative diseases, and all-cause mortality [9].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The reported prevalence of vitamin D deficiency following hip fracture, dependent on racial groups and gender, ranges from 65.8 to 96.7% [20,21] and, in up to 32% of cases, is complicated by secondary hyperparathyroidism (PTH > 5.25 pmol/L in the presence of hypovitaminosis D). Furthermore, soon after hip fracture surgery (at 2 weeks), 25-OHD levels can decrease after hip fracture despite standard oral vitamin D treatment (of 1000 IU daily) compared with higher replacement doses (Figure 2 [10]).…”
Section: Prevalence Of Vitamin D Deficiency Following Hip Fracture Sumentioning
confidence: 99%